2013
DOI: 10.1016/j.tree.2013.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Does the terrestrial biosphere have planetary tipping points?

Abstract: Tipping points-where systems shift radically and potentially irreversibly into a different state-have received considerable attention in ecology. Although there is convincing evidence that human drivers can cause regime shifts at local and regional scales, the increasingly invoked concept of planetary scale tipping points in the terrestrial biosphere remains unconfirmed. By evaluating potential mechanisms and drivers, we conclude that spatial heterogeneity in drivers and responses, and lack of strong continent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
163
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(167 citation statements)
references
References 67 publications
(53 reference statements)
3
163
0
1
Order By: Relevance
“…1 Accordingly, there is a lively debate is on the size of climate damages we may su er (see e.g. Stern, 2007;IPCC, 2014;Nordhaus, 2014), and on the likelihood and e ects of overcoming tipping points in the Earth biophysical system (Greiner et al, 2010;Brook et al, 2013;Grune et al, 2015). 2 The impact of climate change and the design of adaptation and mitigation policies is commonly performed in climate economics by relying on integrated assessment models (IAMs), 3 which add a simple carbon cycle module to a computable general equilibrium barebone (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1 Accordingly, there is a lively debate is on the size of climate damages we may su er (see e.g. Stern, 2007;IPCC, 2014;Nordhaus, 2014), and on the likelihood and e ects of overcoming tipping points in the Earth biophysical system (Greiner et al, 2010;Brook et al, 2013;Grune et al, 2015). 2 The impact of climate change and the design of adaptation and mitigation policies is commonly performed in climate economics by relying on integrated assessment models (IAMs), 3 which add a simple carbon cycle module to a computable general equilibrium barebone (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a mixed reaction from the academic community, who have raised concerns about the existence of global tipping points for some of the dimensions (15)(16)(17) and the specific metrics used (18)(19)(20)(21)(22)(23), the planetary boundaries concept has been used in proposals for defining the UN Sustainable Development Goals (SDGs) (24)(25)(26). The SDGs will guide the international sus-…”
mentioning
confidence: 99%
“…The validity of framing the boundary in terms of extinction rates has been much debated [34,58]. Rockström et al [1] themselves concluded that 'science is, as yet, unable to provide a boundary measure that captures, at an aggregate level, the regulating role of biodiversity' and suggested that extinction rate is only an interim proxy indicator.…”
Section: Defining and Measuring The Safe Operating Spacementioning
confidence: 99%